Genetic influences on economic preferences - David Cesarini; Christopher T. Dawes; Magnus Johannesson; Paul Lichtenstein; Björn Wallace (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
In this paper, we use the classical twin design to provide estimates of genetic and environmental influences on experimentally elicited preferences for risk and giving. Using standard methods from behavior genetics, we find strong prima facie evidence that these preferences are broadly heritable and our estimates suggest that genetic differences explain approximately twenty percent of individual variation. The results thus shed light on an important source of individual variation in preferences, a source which has hitherto largely been neglected in the economics literature.
Keywords: C90; D01; D64; 330; Genetics; Altruism; Risk Aversion; Preferences; Experiments; Risikopräferenz; Altruismus; Schätzung; Präferenztheorie; Biologie; Schweden